Influence of polymer flexibility on nanoparticle dynamics in semidilute solutions. Issue 6 (16th November 2018) - Chen, Renjie; Poling-Skutvik, Ryan; Howard, Michael P.; Nikoubashman, Arash; Egorov, Sergei A.; Conrad, Jacinta C.; Palmer, Jeremy C.
Abstract : The effects of polymer stiffness on nanoparticle dynamics in solution are probed using multi-particle collision dynamics simulations and mode-coupling theory. Abstract : The hierarchical structure and dynamics of polymer solutions control the transport of nanoparticles (NPs) through them. Here, we perform multi-particle collision dynamics simulations of solutions of semiflexible polymer chains with tunable persistence length l p to investigate the effect of chain stiffness on NP transport. The NPs exhibit two distinct dynamical regimes – subdiffusion on short time scales and diffusion on long time scales. The long-time NP diffusivities are compared with predictions from the Stokes–Einstein relation (SER), mode-coupling theory (MCT), and a recent polymer coupling theory (PCT). Increasing deviations from the SER as the polymer chains become more rigid ( i.e. as l p increases) indicate that the NP motions become decoupled from the bulk viscosity of the polymer solution. Likewise, polymer stiffness leads to deviations from PCT, which was developed for fully flexible chains. Independent of l p, however, the long-time diffusion behavior is well-described by MCT, particularly at high polymer concentration. We also observed that the short-time subdiffusive dynamics are strongly dependent on polymer flexibility. As l p is increased, the NP dynamics become more subdiffusive and decouple from the dynamics of the polymer chain center-of-mass. We posit that these effects are due to differences in the segmental mobility of the semiflexible chains.